New optical soliton solutions to magneto-optic waveguides - Rezazadeh, Hadi; Ali, Khalid K.; Sahoo, S.; Vahidi, Javad; İnç, Mustafa (Springer, 2022)
In this article, based on the concepts of the extended tanh expansion method, the general nonlinear magneto-optic waveguides that maintain parabolic-nonlocal law of refractive index is discussed. Then, the physical properties and structures of these obtained solutions are analyzed by means of some graphics. The obtained results can be used in describing the substantial understanding of the studious structures as well as other related non-linear physical structures.
Keywords: Optical soliton; Magneto-optic waveguides; Extended tanh expansion method